Artificial Intelligence – Subject and Actor of Value Space - Belikova, Evgeniya K. (Russian studies in culture and society, 2025)
The article is devoted to the analysis of the role of artificial intelligence (AI) in the social, cultural and value space. It is noted that the initial status of AI as a technological phenomenon was the status of an object influenced by a person who created it and sets its action parameters. Using methods of analysis, synthesis, observation, description, interpretation and others, it is revealed that AI occupies a special position in comparison with other technological phenomena, having ceased to be only an object of the value space, having become a cultural phenomenon and having acquired the properties of a subject. AI itself has value, transmits a number of values ​​(technological efficiency, knowledge, intelligence, education, science, ideas, creativity, etc.). In this, as well as in the formation of the AI ​​culture as a special cultural layer, the subjectivity of AI in the value space is manifested. Further development of AI as a component of the value space is manifested in the fact that it is developing the properties of an actor. According to the actor-network theory of B. Latour, AI is a full-fledged actor of the social space, interacting with other actors and being an active agent. In the value space, the role of an actor is not fully performed by AI in its weak version. This role would be fully performed by a strong AI, which has not yet been created. It is concluded that AI is a complex phenomenon of the cultural field, combining the role of an object, subject and actor of the value space.